DESIGN AND DEVELOPMENT OF SOLID LIPID NANOPARTICLES CONTAINING ROSUVASTATIN USING CENTRAL COMPOSITE DESIGN - DUTTA, DISHARI; CHAKRABORTY, PRANABESH; HOSSAIN, CHOWDHURY MOBASWAR (International Journal of Applied Pharmaceutics, 2025)
Objective: Rosuvastatin calcium, a BCS class II drug with low solubility, was optimized using a central composite design to improve its bioavailability. Methods: The study utilized Kolliphor RH 40 as an emulsifier and glyceryl monostearate as a solid lipid in preparing solid lipid nanoparticle dispersion, optimizing formulations based on mean dissolution time and entrapment efficiency. Results: The study analyzed the entrapment efficiency and mean dissolution time of the prepared solid lipid nanoparticles. The range of mean dissolution time was found 7.1+0.5 to 8.9+0.6 h. The highest entrapment efficiency was found to be 90.28%, with a standard deviation of 0.2. The linear model was chosen based on data precision and trend, while the quadratic model was selected for mean dissolution time. The 3D view graph indicated the model/equation followed by the formulations. The optimized formulation had a particle size of 16.16+10 nm and particle size distribution index to 0.729+002, indicating high homogeneity. Transmission electron microscopy images and dynamic light scattering data were in correlation. XRD, DSC used to analyze the drug's transformation into amorphous form. The dissolution profile of different formulations was plotted, and the optimized formulation followed the Korsmeyer-Peppas model. FTIR showed drug peaks, indicating no interaction. Conclusion: The study suggested that the bioavailability of rosuvastatin calcium can be enhanced through the preparation of solid lipid nanoparticles of smaller size and sustained release of rosuvastatin.